Análisis a los estados financieros de la empresa Skandinar s.a. de la ciudad de Ambato, provincia de Tungurahua período 2013-2014 - Montesdeoca Montesdeoca, Teresa Lourdes (2017)
The thesis entitled analysis to the financial statements of the company S.A. SKANDINAR Ambato city, Tungurahua province period 2013-2014, it conducted to know in general economic and financial position of the aforementioned company, in order to have elements that allow value judgment to make decisions based on real data with the aim of improving its profitability in the medium and long term and position it in the market. Fulfilling the objectives set at the beginning of the work the theoretical basis with the basic guidelines of different subjects met established, along the vertical and horizontal analysis was applied; as well as financial indicators of solvency, indebtedness, liquidity, quality debt payment deadline and economic profitability, necessary for structuring professional criteria with respect to financial balance, to finally issue the respective report it provided information on the financial performance and economic for decision making. It concluded in-depth analysis of the financial situation in which the company is Skandinar S.A. which will serve as a tool for economic and financial pre concurrent or subsequent correction, taking into account the financial indicators.